Variation and Character Association for Various Pulp Biochemical Traits in Tamarindus indica L. - Divakara, B. N. (Indian Forester, 2009)
Thirty-five genotypes of Tamarindus indica L. were evaluated to study variability and character association for various pulp biochemical traits as scope for further improvement. Variability studies revealed that none of the genotypes recorded maximum for more than one pulp biochemical trait. Maximum anthocyanin pigment and total tartaric acid was expressed by TI-32 (1.566 mg/100g) and TI-5 (20.60%) respectively. Total phenol and anthocyanin pigment expressed high heritability coupled with high genetic gain. Correlation studies indicated an inherent association between the characters with most of the traits having negative correlation with total tartaric acid content. Pigment anthocyanin showed negative and highly significant correlation with moisture content at genotypic level. In path coefficient analysis total sugars, total phenol, protein, ash, moisture, total soluble solids showed positive direct effect on total tartaric acid content.